3D Ag(I) coordination polymer constructed from a flexible pyridyloxycyclotetraphoshazene linker: Synthesis, crystal structure and dye adsorption properties - Davarci, Derya; Duyar, Ceyda; Zorlu, Yunus (Pergamon-Elsevier Science Ltd, 2023)
The reaction of the flexible polydentate ligand octakis(3-pyridyloxy)cyclotetraphosphazene (O3PyCP) with AgNO3 afforded a new coordination polymer, [Ag2(O3PyCP)](NO3)2]n (1). The resultant coordination polymer was characterized by single-crystal X-ray crystallography and infrared spectroscopy. The ligand O3PyCP acts in the kappa 6N coordination mode by connecting six Ag(I) ions to form a 3D coordination framework. Topological analysis confirms that compound 1 shows a 3D structure with a fsc topology with the vertex symbol of {44.610.8} {44.62}. The thermal stability of O3PyCP and compound 1 were investigated by thermogravimetric analysis. The study of dye adsorption by tetracyclophosphazene-based coordination polymers was carried out for the first time in this study. According to dye adsorption studies, compound 1 adsorbs anionic methyl orange (MO) from water, but does not exhibit any adsorption behaviour toward cationic methylene blue (MB). A pseudo-second-order kinetic model is suitable to explain the adsorption kinetics.
Keywords: Cyclotetraphosphazene; Ag(I) coordination polymer; Dye adsorption; Methyl orange